A review on selected herbal plants as alternative anti-diabetes drugs: chemical compositions, mechanisms of action, and clinical study - Mustofa Ahda; Irwandi Jaswir; Alfi Khatib; Qamar Uddin Ahmed; Nurkhasanah Mahfudh; Yunita Dewi Ardini (International Journal of Food Properties)
Herbal utilization, as an antidiabetes agent, is an interesting topic to find acceptable herbal drugs to decrease blood glucose levels. The aim of this review is to evaluate the potency of selected herbal medicines to reduce blood glucose levels and to identify the chemical compounds responsible for reducing glucose. The mechanisms of action of different herbal medicines used might be also different. The reduction of blood glucose levels by Aloe vera, Andrographis paniculata, and Trigonella foenum-graecum through minimum 3 mechanisms of action, such as increased GLP-1 secretion and inhibited amylase, glucosidase, and SGLT 2. While Andrographis paniculata has more than 4 mechanisms of action, such as increasing GLP secretion, activating PPAR ɣ-receptor, and also inhibiting amylase, glucosidase, and SGLT 2 but it did not inhibit DPP 4 in diabetic patients.